Building a Culture of Independent Learning in Junior High School Students Through a Self-Management Training Program - Meylida Girsang; Khansa Khalishah; Maretta Selvana Siburian; Toras Pangidoan; Erikson Damanik (Jurnal Pengabdian Masyarakat Variasi, 2026)
A culture of independent learning is a crucial competency for junior high school students, supporting both academic success and character development. However, many students still rely heavily on guidance from teachers and parents to manage their learning processes. This community service initiative aims to foster a culture of independent learning through a self-management training program covering concepts such as self-management, goal setting, time management, self-control, and the evaluation of learning outcomes. Implementation methods included a needs assessment, material delivery via interactive lectures, discussions, simulations, practical exercises in creating study schedules, and ongoing guidance. Evaluation was conducted using observations, questionnaires, and participant reflections to measure improvements in understanding and changes in study habits. The results indicate an increased understanding of the importance of self-management, improved skills in setting study targets and schedules, and a growth in motivation and responsibility regarding independent learning. The training program positively influenced the development of study habits that are more structured, disciplined, and goal-oriented. Consequently, self-management training serves as an effective strategy for fostering a culture of independent learning among junior high school students and warrants sustainable implementation through collaboration between schools, teachers, and parents.